Universities and Cities in Provincial Russia - G. E. Zborovsky; P. A. Ambarova (Высшее образование в России, 2019)
The analysis of higher education (HE) inRussiafocuses on the complicated issues of the relationships between higher education institutions (HEIs) and provincial cities. The authors characterize different typologies of Russian HEIs and cities. It is suggested to distinguish between the HEIs related to the core of HE, semi-periphery, and to the periphery. The situation of peripheral HEIs that are located mainly in provincial cities seems to be the most complicated. Recently, about 300 HEIs and more than 800 branches of universities, a significant part of which belongs to the peripheral group, ceased to exist autonomously. Today the fate of some other provincial HEIs is yet to be defined. Meanwhile, the future of the young people is also tied to the HEIs’s destiny as well as the future of the cities’ population, where they are located. The analysis of the materials based on the authors’ empirical research conducted in the Ural Federal District (UFD) revealed that the elimination of autonomous universities, their transformation into branches and weakening in such a way of the HE in the medium, big and even large cities of the Russian province lead to stagnation and depression of these cities. One of the main factors of this situation is the mass educational migration of young people. The study discusses certain ideas for positive solution of these problems regarding the relationship of provincial Russian universities and cities, which could lead to their preservation and development.